Implicit Shame and Avoidant Interpersonal Style: The Mediating Role of Identity Fragility - Schneider, Lukas; Gong, Jiaowei (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the mediating role of identity fragility in the relationship between implicit shame and avoidant interpersonal style among young adults in Vietnam. Methods and Materials: The research employed a descriptive correlational design with a sample of 424 university students from Vietnam, selected using the Morgan and Krejcie sampling table. Data were collected through standard tools: the Implicit Association Test for Shame (IAT-Shame), the Self-Concept Clarity Scale (SCCS) to assess identity fragility, and the Attachment Style Questionnaire (ASQ) for measuring avoidant interpersonal style. Descriptive statistics and Pearson correlation analyses were performed using SPSS-27 to examine bivariate relationships. Structural Equation Modeling (SEM) was then conducted in AMOS-21 to test the proposed mediation model, and model fit was evaluated using a range of fit indices. Findings: The results of Pearson correlation showed significant positive relationships between implicit shame and identity fragility (r = .47, p < .001), implicit shame and avoidant interpersonal style (r = .39, p < .001), and identity fragility and avoidant interpersonal style (r = .52, p < .001). The structural equation model showed good fit (χ² = 132.48, df = 74, χ²/df = 1.79, RMSEA = 0.043, CFI = 0.97). Path analysis revealed that implicit shame had a significant direct effect on identity fragility (β = .47, p < .001) and on avoidant interpersonal style (β = .19, p = .004). The indirect effect of implicit shame on avoidant interpersonal style through identity fragility was also significant (β = .21, p < .001), confirming the mediating role. Conclusion: These findings highlight the importance of implicit shame and unstable identity structures in shaping avoidant relational behaviors, emphasizing the need for psychological interventions that address unconscious emotional vulnerabilities and promote identity coherence.